Design of lipid nanoparticle (LNP) containing genetic material CRISPR/Cas9 for familial hypercholesterolemia - Prasetia, I GNJA.; Kurniati, Neng F.; Riani, Catur; Mudhakir, Diky (Narra Sains Indonesia, 2025)
Familial hypercholesterolemia is a genetic disorder caused by mutations in the low-density lipoprotein receptor gene (LDLR) and the current treatment still focuses on symptom management. The aim of this study was to develop a lipid nanoparticle (LNP)-based delivery system for the CRISPR/Cas9 component in correcting LDLR gene mutations. LNPs were prepared using an ultrasonic-solvent emulsification technique by varying the surfactant: oil ratio (SOR), homogenization speed and time, and sonication time. Next, the LNP surface was modified by adding DSPE-PEG2000-NH2 and polyethyleneimine. The next stage is to design the single guide RNA (sgRNA) and Donor DNA wildtype (Donor DNA wt). This genetic material was complexed with LNP and then transfected into Hepa1-6 LDLR mt cells, an in vitro representation of cells suffering from familial hypercholesterolemia. This optimization process produced LNPs with a particle size of 118.6±0.8 nm and a polydispersity index of 0.34±0.03. The LNP surface modification resulted in a zeta potential of +7.5 mV. A transmission electron microscope (TEM) analysis howed spherical morphology with size distribution following a regular pattern. LNP cell viability tests showed good biocompatibility at concentrations <15 mM with a half-maximal inhibitory concentration (IC50) value of 27.7 mM. The dominant cellular uptake mechanism of LNP was through the clathrin-mediated endocytosis (CME) pathway. The Hepa1-6 LDLR mt cell model was successfully produced with the transfecting agent Lipofectamine 3000 by homology-directed repair (HDR) mechanism. The LNP-genetic material complex with a ratio of sgRNA:Cas9:Donor DNA wt (1:1:0.04) showed an increase in LDLR gene expression of 3.3±0.2 times and LDLR protein levels reached 12.95±0.25 ng/mL on day 4 after transfection. The results of this study indicate that the developed LNP-based delivery system has the potential for gene therapy applications in familial hypercholesterolemia.